Investigating the Relationship between Porosity and Compressive Strength for Porous Concrete as a Sustainable Pavement - Hassan Tajik Ghashghaei; Abolfazl Hassani; Morteza Ahmadi (The Global Environmental Engineers, 2015)
In this study, the relationship between porosity and compressive strength for porous concrete (PC) was investigated. The effect of mixture design parameters particularly, water-to-cement ratio (W/C) and size of aggregate on the porosity and compressive strength of PC was evaluated. To investigate the role of W/C and aggregate size on this testing procedure, the experiments were performed on specimens of two aggregates size and four range of W/C. The PC mixtures were made with W/C in the range of 0.28-0.34, 350kg/m3 cement content and 19.5mm and 9.5 maximum size of aggregate. PC mixes were made from each aggregate and were tested. The results showed that the W/C and aggregate size are key parameters which significantly affect the porosity of PC. Investigation of compressive strength and porosity for the various mix designs showed a clear dependence on these parameters. The measured values fall within the expected range obtained from a review of the literature. Compressive strength of coarse porous concrete (CPC) is smaller than compressive strength of fine porous concrete (FPC) and the porosity of CPC are bigger than porosity of FPC. In general, increased W/C yields a smaller porosity and higher compressive strength. This approach can reduce the number of trial batches needs for target performance of PC samples.